Formalization of correlational studies of water problems - Javier Carreon Guillen; Cruz García Lirios; Celia Yaneth Quiroz Campas; Elías Alexander Vallejo Montoya; Francisco Espinoza Morales; Victor Hugo Meriño Córdoba; Carmen Ysabel Martínez de Meriño; Luiz Vicente Ovalles Toledo; Clara Judith Brito Carrillo; Arger Verstapp Bund (Journal of Model Based Research, 2023)
A methodological note proposes formal structures for correlational studies of water problems. It emphasizes variable definition, confounding control, and reproducibility.
Keywords: Conformity